2018
DOI: 10.1177/1055665618775866
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning of Children in a Craniofacial Support Group

Abstract: Objective: To describe psychosocial functioning before and after participation in support groups for pediatric patients with craniofacial diagnoses and their families. Design: Baseline and postgroup outcomes and comparison to test norms.Setting: Urban children's hospital. Participants: Patients (N ¼ 138) were 54% female, primarily Latino (83%), aged 7 to 18 years (mean ¼ 10.4, standard deviation ¼ 2.8), and had public insurance (72%). Patients had isolated cleft lip/palate (54%), craniofacial syndromes (19%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Studies have proposed resiliency and social skills training for young adults with CFCs as potential interventions to improve QoL, psychological well-being, and the ability to cope in difficult situations (Kapp-Simon et al, 2005; Topolski et al, 2005; Rumsey and Harcourt, 2007; Feragen et al, 2009; Bessell et al, 2012; Johns and Bava, 2019). Kapp-Simon et al (2005) investigated the effect of social skills training on social interactions among adolescents with CFCs and found that those in the social skills training had a greater increase in the overall rate of social interactions and were 3 times more likely to engage in a conversation with their peers than they were before starting the group.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have proposed resiliency and social skills training for young adults with CFCs as potential interventions to improve QoL, psychological well-being, and the ability to cope in difficult situations (Kapp-Simon et al, 2005; Topolski et al, 2005; Rumsey and Harcourt, 2007; Feragen et al, 2009; Bessell et al, 2012; Johns and Bava, 2019). Kapp-Simon et al (2005) investigated the effect of social skills training on social interactions among adolescents with CFCs and found that those in the social skills training had a greater increase in the overall rate of social interactions and were 3 times more likely to engage in a conversation with their peers than they were before starting the group.…”
mentioning
confidence: 99%
“…Kapp-Simon et al (2005) investigated the effect of social skills training on social interactions among adolescents with CFCs and found that those in the social skills training had a greater increase in the overall rate of social interactions and were 3 times more likely to engage in a conversation with their peers than they were before starting the group. Similarly, Johns and Bava (2019) compared baseline and postgroup psychosocial functioning to test norms among pediatric patients, aged 7 to 18, who completed support groups for those with CFCs. They found that postgroup participants reported significantly lower social stress than peer norms and participants displayed significant improvements in psychosocial functioning after completing the groups, including adaptive skills, self-esteem, and social stress (Johns and Bava, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…People with high self-efficacy are observed to be more persistent in their efforts to manage threatening situations (King et al, 1993). Studies of populations with a cleft employing indirect measures of self-efficacy, such as self-confidence (Stock and Ridley, 2018), self-concept (King et al, 1993), belief in adaptive and control skills (Johns and Bava, 2019), and social problem-solving ability (Snyder and Pope, 2010;Feragen et al, 2017), have shown lower levels of these variables in children and adolescents with CL/P, consistent with the lower total self-efficacy score found in our results. However, this difference had a relatively small effect size and the total score was similar to a Spanish public school population (Carrasco Ortiz and del Barrio Gándara, 2002) and better self-efficacy was reported by the participants with a cleft for academic self-efficacy and self-regulation compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that children from the ages of three to five years were found to have a self-concept that is similar to the others that do not have a cleft. There have been higher levels of anxiety and more dissatisfaction among children through relationships with their peers as they grow older which can be due to possible speech impediments and the associated stigma of visible deformities [10]. During preschool years, the relationship between a child's self-concept and parental attitudes is very important.…”
Section: Discussionmentioning
confidence: 99%